Estudo da estabilidade da beta-galactosidase imobilizada de Bacillus licheniformis e aplicação em reator de leito fixo - Lafia, Aliou Toro (2023)
Dairy products are some of the most complete and widely consumed foods. Lactose intolerance in a large part of the world population leads to the production of products without or with reduced lactose content using β-galactosidase. Enzyme immobilization is a process that allows the recovery and reuse of this biocatalyst, besides increasing its operational stability. In this work, the stability of β-galactosidase from Bacillus licheniformis immobilized by adsorption on Duolite A-568 resin at room temperature (approximately 25°C), BR buffer with ionic strength of 40 mM and pH 4.0 and enzyme concentration of 43 mL/L was studied. The immobilized enzyme was cross-linked with glutaraldehyde at different concentrations (2.0 to 3.5 g/L). The stability of the immobilized biocatalyst was evaluated with respect to pH in the range of 3 to 8, temperature in the range of 30 to 60°C, and storage for 90 days. The activation energy of the thermal deactivation process of the immobilized enzyme was also determined. The conversion rate of lactose by immobilized and immobilized cross-linked enzyme in a batch reactor with recirculation and different feed rates was evaluated. The results of yield, efficiency and recovered activity of immobilized β galactosidase were 84%, 99% and 83%, respectively. The glutaraldehyde concentration of 2.0 g/L provided better stability, maintaining 75% of the initial activity on the sixth use, and had its activity unchanged when stored for 35 days. The immobilized enzyme without cross linking presented pH optimum at 4, while the optimum pH range for immobilized enzyme followed by cross-linking (2.0 g/L) was 4 to 7. In relation to thermal stability the immobilized and cross-linked enzyme was more stable than the immobilized enzyme only at all temperatures evaluated. The storage affected more the activity of the immobilized enzyme (without crosslinking), which presented a relative activity of 27%, at pH 3 and 4 in 90 days, while the immobilized and crosslinked enzyme retained more than 70% of the initial activity during 90 days in all pH values (3 to 8). The denaturation energy found for the immobilized enzyme without crosslinking and the immobilized enzyme followed by crosslinking were 59,715.32 and 66,063.78 kcal/mol, respectively. Regarding lactose conversion, the cross linked immobilized enzyme was more stable maintaining more than 50% of its initial conversion capacity. With the increase of the flow rate in the order of 2 mL/min a decrease in the conversion rate of about 5% was observed. In general, cross-linking with glutaraldehyde increased the stability of β-galactosidases from Bacillus licheniformis immobilized on Duolite A-568. The immobilized β-galactosidase from Bacillus licheniformis can be applied in various processes of hydrolysis or lactose conversion under the studied conditions.